2019
DOI: 10.1093/jamia/ocz044
|View full text |Cite|
|
Sign up to set email alerts
|

An electronic health record–based interoperable eReferral system to enhance smoking Quitline treatment in primary care

Abstract: Objective The study sought to determine whether interoperable, electronic health record–based referral (eReferral) produces higher rates of referral and connection to a state tobacco quitline than does fax-based referral, thus addressing low rates of smoking treatment delivery in health care. Materials and Methods Twenty-three primary care clinics from 2 healthcare systems (A and B) in Wisconsin were randomized, unblinded, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Yet, more progress is needed as evidenced by relatively low tobacco treatment program reach in some settings, even using a broad definition of engagement. However, average reach rate in the C3I programs (about 25%) should be interpreted in light of the fact that reach rates for tobacco treatment in primary care settings are typically 15% or much lower (26,27). At baseline, even among these highly resourced NCI-Designated Comprehensive Cancer Centers, only one Center had already implemented automatic EHR-based referrals to tobacco treatment for all patients who smoke.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, more progress is needed as evidenced by relatively low tobacco treatment program reach in some settings, even using a broad definition of engagement. However, average reach rate in the C3I programs (about 25%) should be interpreted in light of the fact that reach rates for tobacco treatment in primary care settings are typically 15% or much lower (26,27). At baseline, even among these highly resourced NCI-Designated Comprehensive Cancer Centers, only one Center had already implemented automatic EHR-based referrals to tobacco treatment for all patients who smoke.…”
Section: Resultsmentioning
confidence: 99%
“…The Helpline treatment reach of 61% is comparable or higher than others reported in the clinical trials by Vidrine et al (68.7%) 26 and Fiore et al (30% connected but not necessarily treated). 12 The similar treatment reach between the Helpline and group class suggest that these offerings are not mutually exclusive and can be promoted concurrently. Our treatment reach (1.6%) is higher than the ask-advise-refer group (0.5%) but lower than an ask-advise-connect group (14%) in a study by Vidrine et al 26 This may reflect our inclusion of inpatient eReferrals which had lower rates of accepting services.…”
Section: Discussionmentioning
confidence: 99%
“…4,36 Even the "complete case" quit rate of 21.9% may reflect an underestimate of the higher range, as only half of the patients who had a eReferral had a follow-up clinic visit within the year. 12,26 We did not measure utilization of medications, which may improve quit rates, as these may not have been prescribed and documented in the EHR but used over the counter. There was also a concurrent Helpline offer for free nicotine patches mailed directly to patients in the Medi-Cal Incentives to Quit Smoking project (2012-2015) 30 which would also not have been documented in the EHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence, however, that with this approach, the QL is unable to contact and/or keep enrolled a large percentage of the patients who agree to be connected (12,(14)(15)(16). Adsit et al found that among tobacco users consenting to be eReferred to the QL, 64.8% later declined cessation services (14).…”
Section: Introductionmentioning
confidence: 99%